Do Re Mi: Psikologi, Musik, dan Budaya - Rinanda Rizky Amalia Shaleha (Faculty of Psychology Universitas Gadjah Mada, 2019)
Music has been a part of everyday human life since ancient times. Music can influence how humans feel, think, and behave. Scientific evidence also shows that there is a neurobiological basis of music. The universality of music makes everyone able to sense the emotional content in music. However, music is a product of culture so it can not be separated from cultural bias. Music is considered as a determinant of social identity. Furthermore, music influences social preferences in society. Music with certain types is considered as a marker of the group so that there is a stereotype in assessing a group. The benefits of music can be obtained in various settings such as in education and health setting. Future studies, it is necessary to review music from different perspectives such as culture, psychology, and neurobiology to be more comprehensive in order to explain the influences of music in human life.